PENGARUH EFEKTIVITAS BELAJAR SISWA TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN IPS KELAS VII SMP NEGERI 5 PANJI SITUBONDO SEMESTER GENAP TAHUN PELAJARAN 2015/2016 - Dassucik Dassucik (STKIP PGRI SITUBONDO, 2016)
The current implementation of the curriculum system cannot be separated from the effectiveness of activities on students or directly involving students in learning, students can be actively involved, because they are the center of learning activities and competency building. Students must be involved in directed question and answer and seek solutions to various learning problems. Students should be encouraged to interpret the information provided by the teacher, until the information can be accepted by common sense. The purpose of this study was to determine the effect of learning effectiveness on student learning outcomes in social studies class VII SMP Negeri 5 Panji Situbondo even semester of the 2015/2016 academic year. From the research results obtained using the analysis formula of variance regression lines, the value of Ry (1,2) empiric is 0.60017, which when consulted with the r-table with N of 100 respondents and a significance level of 5%, obtained 0.195. The calculation is intended to prove the major working hypothesis by using a significance test. From the results of the calculation of the analysis of variance of the regression line, it is obtained that the Reg. Is 27.30494. And when consulted with F table for db1 = 2 and db2 = 97 with a significance level of 5%, obtained 3.0902. Thus, the results of these calculations indicate that the F reg value exceeds the F table value. Based on the results of the data analysis, the major work hypothesis which reads